Determinants of retention in care in an antiretroviral therapy (ART) program in urban Cameroon, 2003-2005 - Anne Cecile Zoung-Kanyi; Lucienne Assumpta Bella; Carno Tchuani; Helene Epee; Louis Menyeng; Regis Pouillot; Jembia Mosoko; Claudine Essomba; Yacouba Njankouo Mapoure; Madeleine Mbangue; Therese Abong; Mathurin Tejiokem; et al. (The Pan African Medical Journal, 2008)
Background:Retention in long-term antiretroviral therapy (ART) program remains a major challenge for effective management of HIV infected people in sub-Saharan Africa. Highly Active Antiretroviral Therapy (ART) discontinuation raises concerns about drug resistance and could negate much of the benefit sought by ART programs. Methods:Based on existing patient records, we assessed determinants of retention in HIV care among HIV patients enrolled in an urban ART at two urban hospitals in Cameroon. Extended Cox regression procedures were used to identify significant predictors of retention in HIV care. Results:Of 455 patients, 314 (69%) were women, median (IQR) age and baseline CD4 cell count were respectively 36 years (30 – 43) and 110 cells/µL (39 – 177). Forty patients (9%) had active tuberculosis (TB) at enrollment. After a median (IQR) follow-up of 18 months (10–18), 346 (75%) were still in care, 8 (2%) were known dead, and 101 (22%) were lost to follow-up (LFU). Severe immunosuppression (CD4 cell count ≤ 50 cells/µL) at baseline (aHR 2.3; 95% CI 1.4 - 3.7) and active tuberculosis upon enrollment (aHR 1.8; 95% CI 1.0 - 3.6) were independent predictors of cohort losses to follow-up within the first 6 months after HAART initiation. Conclusion:These data suggest that three-quarter of HIV patients initiated on HAART remained in care and on HAART by 18 months; however, those with compromised immunologic status at treatment initiation, and those co-infected with TB were at increased risk for being lost to follow-up within the first 6 months on treatment.